PENGARUH BOOK TAX DIFFERENCES DAN KINERJA KEUANGAN PERUSAHAAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN DENGAN KAPITALISASI PASAR TEBESAR DI INDONESIA - Yulianto Yulianto; Lindawati Lindawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to determine the effect of book tax differences and company financial performance on profit growth, in companies with the largest market capitalization in Indonesia from 2016 to 2020. This study uses quantitative data types with descriptive analysis test methods and multiple linear regression analysis. The sampling method is done by purposive sampling technique. The results showed that simultaneously book tax differences (BTD), financial performance as proxied by return on assets (ROA) and total asset turnover (TATO) had an effect on profit growth, while partially only return on assets had an effect on growth profit